KINETIC AND EQUILIBRIUM STUDIES OF VANADIUM BIOSORPTION BY A BROWN SEAWEED – IMPLICATIONS TO BIOREMEDIATION OF CONTAMINATED SITES : Life Science-Environmental science - CARLOS AUGUSTO DA COSTA, ANTONIO; DE SOUZA OLIVEIRA, MARCELO; SEVERINO LUNA, ADERVAL (International Journal of Life Science and Pharma Research, 2012)
This paper studied the biosorption of vanadium ions by the brown seaweed Sargassum filipendula. Results obtained indicated that acidic pH values are more favorable to biosorption and that the uptake capacity of the biomass gradually increased with the increase of solid/liquid ration. Additionally it was observed that a rapid equilibrium was reached between solid and liquid fractions, around 20 minutes and that the kinetic behavior could be better explained by a second order reaction. Equilibrium data obtained showed that the results could be fit to Langmuir model, indicating that a monolayer of vanadium was probably formed on the surface of the seaweed. These results opens the possibility of using biosorption as a bioremediation technique for large-scale purposes with the use of fixed-bed reactors.